Effects of personality traits on goal commitment of Greco-Roman and freestyle wrestlers - Çelebi, M.; Sarikabak, M. (African Educational Research Journal, 2020)
The purpose of this study is to investigate the effects of Greco-Roman and Free-Style wrestlers' personality traits on goal commitment. The universe of the research is elite Greco-Roman and Free-Style wrestlers who actively participate in wrestling competitions. The sample group consists of 338 wrestlers, who were selected among these wrestlers with the convenience-sampling method. As data collection tools, "Personal information form" created by the researcher; the Turkish Big Five Inventory developed by John et al. (1991) and adapted to Turkish by Evinç (2004); the scale of "Goal Commitment" prepared by Klein et al. (2001) with the validity and reliability performed by Senel and Yildiz (2016) were used in the research. SPSS 20 package program was used in the statistical analysis of the data. Descriptive statistics, Pearson correlation analysis and simple linear regression analysis were used. As a result of the analyses, the goal commitment points; moderately positive for openness to experience (r = .323; p <.05) and conscientiousness (r = .323; p <.05); There was a low level positive relation between goal commitment and extroversion (r = .295; p <.05) and agreeableness (r = .271; p <.05). Personality traits scores of Greco-Roman and Free-Style wrestlers versus their goal commitment scores, sub-dimensions of openness to experience and conscientiousness were significant predictors of goal commitment and explained 14% of the total variance which has been identified. Similar results were also found in Greco-Roman (11%) and Free-Style (15%) wrestlers.